KERAGAMAN MAKNA POLITIK DAN KEKUASAAN CERPEN âSEPOTONG BIBIR PALING INDAH DI DUNIAâ KARYA AGUS NOOR: KAJIAN SEMIOTIK ROLAND BARTHES - , JUWITA NUR MUSTIKA, Dr. Novi Siti Kussuji Indrastuti, M. Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Research \"Diverse Political and Power Understanding of 'Sepotong Bibir Paling Indah di Dunia' In Short Stories Collection of Sepotong Bibir Paling Indah di Dunia By Agus Noor:Semiotics Review By Roland Barthes\" motivated by the dominance of the personification of style and aesthetics of violence intended to cause parody impressions. Impression parody intended as an expression of political satire on power and Indonesian leaders. Satire about politics and power Indonesian leaders contained in the short story \"Sepotong Bibir Paling Indah di Dunia\" is told using symbols interconnected. These symbols are a means to create a dramatic story and have aesthetic value on the issue of politics and power in this short story. This study aims to reveal the diversity of political meaning and power through translation and interpretation lexia Barthes five codes. The use of these theories are considered most relevant to interpret the meaning of the symbols and stories for reaching out in detail the diversity of meaning contained in the text . Results of this study showed that the short story \"Sepotong Bibir Paling Indah di Dunia\" has a dominant lexia - lexia about politics and power issues in Indonesia. Some lexia - lexia dominant on the political and social problems is shown through several perspectives, the perspective and the perspective of the ruler of the people. The relationship two perspectives show a big theme as the core or center of the story, the critique of power politics and the Indonesian leader. Aesthetic use of violence against a piece of the function and role of the lips lips confirms that serves as the center of the story, a character who dominates, in a power and a key figure in the political representation of the Indonesian government. Symbols contained in the short story as a whole has a diversity of political meaning and power and there is some element of knowledge. Various aspects such as culture, language, the concept of aesthetics, ideology, philosophy of life, history, epistemology, linguistics, semiotics, and psychology is a construction marker codes in the short story.